STRATEGI KOMUNIKASI SATUAN PETUGAS (SATGAS PPKS ) KAMPUS DALAM MENANGANI KASUS PELECEHAN SEKSUAL - Ernawati (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The continued rise in sexual violence in higher education institutions underscores the urgency of strengthening the communication strategy of the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS). This study aims to describe the Task Force's communication strategy in carrying out its function of preventing, handling, and recovering victims of sexual violence on campus. The method used was a qualitative case study design through interviews, Focus Group Discussions, and documentation studies at the PPKS Task Force at Sebelas Maret University and Salatiga State Islamic University. The results show that the Task Force's communication strategy is implemented through standardized and confidential internal coordination, external collaboration with service agencies and law enforcement officials, and the dissemination of gender literacy-based public information. Empathetic and victim-centered communication has been shown to play a significant role in building trust, reducing barriers to reporting, and strengthening a safe campus culture.